THE SOCIAL AND POLITICAL ESSENCE OF IMPLEMENTING INFORMATION TECHNOLOGIES IN THE PUBLIC SECURITY SYSTEM (Scientific journal of the Fergana State University, 2025)
In this article, opinions on the socio-political essence of implementing information technologies in the public security system are scientifically analyzed. Also, the article scientifically highlights that the use of modern information technologies in the field of ensuring public safety is becoming a pressing issue in the context of rapid changes taking place today on a global scale, technological progress, and the digital revolution.